PHOTOCATALYTIC PRODUCTION OF TiO2-NATURAL ZEOLITE FROM TASIKMALAYA FOR PHOTODEGRADATION OF METHYLENE BLUE - Arfan Sani A.; Atiek Rostika N.; Diana Rakhmawaty (Jurnal Zeolit Indonesia, 2009)
Photocatalyst is reaction process of one materials to another materials which aided by energy from ultraviolet radiation and solid catalyst. The study conducted by making a catalyst based on variation concentrates from natural zeolite Cikalong-Tasikmalaya with addition of TiO2. The test of photocatalytic activity was conducted on methylene blue. The purpose this study to obtain a new photocatalytic is modified of natural zeolite with TiO2 which expected had a high reactivity so able to used on waste fluid processing. The step was conducted were activated natural zeolite, than making of photocatalytic from TiO2 and natural zeolite, and the last is drying on the oven and calcination at 5000C. In the diffraction pattern of TiO2-zeolit (20%) there was a peak of TiO2 around of 2Î¸ about 25,3o, it is indicated that TiO2 was surroundings on natural zeolite. TiO2-zeolit (20%) which was analyzed with SEM showed that active metal of TiO2 has been surroundings on surface of zeolite. Analysis of gas absorption (GSA) with BET methods showed an increase wide of 7,0 m2/g for zeolite and19,4 m2/g for TiO2-zeolit (20%). Best degradation of methylene blue was indicated by TiO2-zeolit (20%) with the value of 82,5% after the radiation with ultraviolet for 80 minutes and measured by visible UV spectrophotometer.